Bias Ideologis Tafsir Hizb al-TahrÄ«r - Fawaid, Ahmad; Mardlatillah, Nafi'ah (MAGHZA, 2020)
This article figures out ideological biases in AbÅ« Rashtah Bookâ€™s, al-TaysÄ«r fÄ« 'UlÅ«m al-TafsÄ«r: Tafsir al-Baqarah. As a figure of á¸¥izb al-taá¸¥rÄ«r, AbÅ« Rashtah's interpretation strengthens his organization's ideology and to oppose the ulama's interpretation. This article questions how the al-TaysÄ«r methodology was used by AbÅ« Rashtah for interpreting al-Qur'an and how the biases of AbÅ« Rashtah's interpretation in his book. By using thematic writing techniques on khilÄfah verses and using descriptive analysis methods, This research concludes that the method of interpretation applied in his book prioritizes linguistic analysis and the use of reason. Through this method of language based on reason, it was found that there were ideological biases. One of them is the persuasion of the enforcement of the khilÄfah Islamiyyah system when he interprets the QS. Al-Baqarah: 30. AbÅ« Rashtah is of the view that this verse is the normative basis for the enforcement of the khilÄfah system. Apart from the above verse, the invitation to enforce the khilÄfah system can also be found in the QS interpretation of al-Baqarah: 105. AbÅ« Rashtah believes that the KhilÄfah Islamiyyah will soon be established on the face of the earth according to Allah's promise.